A QUALITATIVE APPROACH TO THE LEVEL OF EMPLOYMENT, UNDEREMPLOYMENT AND UNEMPLOYMENT IN LIMA - Ramírez Miranda, Ridberth (2012)
This research aims to find, explain and describe the procedures for analysis of impact indicators on the levels of employment, underemployment and unemployment, as well as significant other indicators such as the population of working age (PET) and the economically active population (PEA). Based on the construction and analysis of indicators, such as employment, unemployment and underemployment rates which in reality turn out to be frequent indicators of the laboral market. We can identify through them changes in the labor market of a country. In the development of this research, concepts are explained on the reference period and the minimum age, in order to identify the condition of activity, the active search in the case unemployment, the one hours criterion typifying the busy, and the minimum benchmark, as a limit to characterize the invisible underemployed person among other things. Consequently, there is interest in assessing the concrete reality and validity of the calculation methodologies, and considering the observations submitted within their results, which relate to the level of employment rates, underemployment and unemployment and Punjab, however, these are the product of the same procedures used by countries in the region, also recommended by the International Labor Organization (ILO). To measure rates of employment, unemployment and underemployment of this investigation, we have used data collected by the National Household Survey (ENAHO) in Metropolitan Lima and Callao. Finally, we proceeded with a qualitative analysis of the data collected.